PDE3-inhibitor enoximone prevented mechanical ventilation in patients with SARS-CoV-2 pneumonia. (16th March 2021) - Beute, Jan; Boermans, Pieter; Benraad, Bart; Telman, Jan; Diamant, Zuzana; KleinJan, Alex
Abstract: Background: Standard care in severe SARS-CoV-2 pneumonia complicated by severe dyspnea and respiratory failure, consists of symptom reduction, ultimately supported by mechanical ventilation. Patients with severe SARS-CoV-2, a prominent feature of COVID-19, show several similar symptoms to Critical Asthma Syndrome (CAS) patients, such as pulmonary edema, mucus plugging of distal airways, decreased tissue oxygenation, (emergent) exhaustion due to severe dyspnea and respiratory failure. Prior application of elective phosphodiesterase (PDE)3-inhibitors milrinone and enoximone in patients with CAS yielded rapid symptomatic relief and reverted the need for mechanical ventilation, due to their bronchodilator and anti-inflammatory properties. Based on these observations, we hypothesized that enoximone may be beneficial in the treatment of patients with severe SARS-CoV-2 pneumonia and prominent CAS-features. Methods: In this case report enoximone was administered to four consecutive patients (1 M; 3 F; 46–70 y) with emergent respiratory failure due to SARS-CoV-2 pneumonia. Clinical outcome was compared with three controls who received standard care only. Results: After an intravenous bolus of enoximone 20 mg followed by 10 mg/h via perfusor, a rapid symptomatic relief was observed: two out of four patients recovered within a few hours, the other two (with comorbid COPD GOLD II/III) responded within 24–36 h. Compared to the controls, in the enoximone-treated patients respiratory failure and further COVID-19-related deterioration was reverted and mechanical ventilation was prevented, leading to reduced hospital/ICU time. Discussion: Our preliminary observations suggest that early intervention with the selective PDE3-inhibitor enoximone may help to revert respiratory failure as well as avert mechanical ventilation, and reduces ICU/hospital time in patients with severe SARS-CoV-2 pneumonia. Our findings warrant further research on the therapeutic potential of PDE3-inhibition, alone or in combination with other anti-COVID-19 strategies.